IMPLEMANTASI MANAJEMEN SARANA PRASARANA DALAM MENINGKATKAN LULUSAN SISWA DI SEKOLAH DASAR NEGERI TANJUNG BINJE KECAMATAN BENDAHARA KABUPATEN ACEH TAMIANG - Wahyuni, Adinda Alvina; Syahputri, Eka; Ramadhan, Muhammad Fiqri; Thasfa, Saida Amini (IKAMAS: Manajemen Pendidikan Islam, 2022)
One of the factors that determine the graduation rate of students in a school is the facilities and infrastructure. Educational facilities and infrastructure can help students learn comfortably. The success of the teaching and learning process requires both teachers and facilities and infrastructure to achieve it. This study aims to describe the implementation of facilities and infrastructure management. infrastructure at SD Negeri Tanjung Binje Kec. Bendahara Kab.Aceh Tamiang in improving student graduates at the school.